Flavanol-Rich Cocoa Supplementation Inhibits Mitochondrial Biogenesis Triggered by Exercise - Jose Angel García-Merino; Beatriz de Lucas; Karen Herrera-Rocha; Diego Moreno-Pérez; Maria Gregoria Montalvo-Lominchar; Arantxa Fernández-Romero; Catalina Santiago; Margarita Pérez-Ruiz; Mar Larrosa (MDPI AG, 2022)
The potential role of cocoa supplementation in an exercise context remains unclear. We describe the effects of flavanol-rich cocoa supplementation during training on exercise performance and mitochondrial biogenesis. Forty-two male endurance athletes at the beginning of the training season received either 5 g of cocoa (425 mg of flavanols) or maltodextrin (control) daily for 10 weeks. Two different doses of cocoa (equivalent to 5 g and 15 g per day of cocoa for a 70 kg person) were tested in a mouse exercise training study. In the athletes, while both groups had improved exercise performance, the maximal aerobic speed increased only in the control group. A mitochondrial DNA analysis revealed that the control group responded to training by increasing the mitochondrial load whereas the cocoa group showed no increase. Oxidative stress was lower in the cocoa group than in the control group, together with lower interleukin-6 levels. In the muscle of mice receiving cocoa, we corroborated an inhibition of mitochondrial biogenesis, which might be mediated by the decrease in the expression of nuclear factor erythroid-2-related factor 2. Our study shows that supplementation with flavanol-rich cocoa during the training period inhibits mitochondrial biogenesis adaptation through the inhibition of reactive oxygen species generation without impacting exercise performance.